On the Stability of Numerical Methods for Nonlinear Volterra Integral Equations - E. Messina; Y. Muroya; E. Russo; A. Vecchio (Discrete Dynamics in Nature and Society)
Here we investigate the behavior of the analytical and numerical solution of a nonlinear second kind Volterra integral equation where the linear part of the kernel has a constant sign and we provide conditions for the boundedness or decay of solutions and approximate solutions obtained by Volterra Runge-Kutta and Direct Quadrature methods.